Manajemen Pembiayaan Pendidikan dalam Meningkatkan Keberlanjutan Lembaga Pendidikan Islam: Analisis Annual Report 2024 Australian International Islamic College - Avifahtur Nur Rohma; Salsabila Qurratu’ain ‘Abidah; Muhammad Munadi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the educational financing management of Australian International Islamic College (AIIC) based on its 2024 Annual Report. The research employed a qualitative approach using a document analysis method. Data were obtained from the AIIC Annual Report 2024, which contains information on the institution’s profile, student characteristics, human resources, community engagement, and financial statements. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that AIIC has a financing system supported by diversified revenue sources, including funding from the Australian Government, state governments, tuition fees, and other private income. In 2024, AIIC generated a total revenue of AUD 31,065,874 and recorded total expenditures of AUD 27,054,143. The largest proportion of the budget was allocated to personnel costs and educational operational expenses. In addition, AIIC invested AUD 91,000 in professional development programs for educators as part of its efforts to enhance educational quality. The effectiveness of AIIC’s financing management is reflected in its high student retention rate of 88.33%, stable student attendance rates exceeding 91%, and the increasing number of graduates admitted to leading universities across Australia. This study concludes that effective, transparent, and quality-oriented financial governance plays a crucial role in maintaining the sustainability of modern Islamic educational institutions. The findings suggest that diversified funding sources, strategic investment in human resources, and sound financial management practices contribute significantly to improving educational quality and institutional performance